A simple method for automatic brain extraction from T1-W Magnetic Resonance Images (MRI) of human head scans - Ezhilarasan, K; Somasundaram, K. Somasundaram; Kalaiselvi, T (International Journal of Computer Sciences and Engineering, 2025)
A simple method to extract brain portion from T1-Weighted Magnetic Resonance Image (MRI) of human head scans is proposed in this article. The proposed method employs mean filter and morphological operations. This method is experimented on five volumes of normal T1-W MRI of human head scans taken from the Internet Brain Segmentation Repository (IBSR). The chosen method gives comparable results with the existing popular methods such as Brain Extraction Tool (BET) and Brain Surface Extractor (BSE). The performance of the proposed method is evaluated using Jaccard (J) similarity index and Dice coefficient (D) and a corresponding mean value of 0.936 and 0.965 is obtained